Morphological plasticity in a native freshwater fish from semiarid Australia in response to variable water flows. Issue 16 (20th July 2017) - Kelley, Jennifer L.; Davies, Peter M.; Collin, Shaun P.; Grierson, Pauline F.
Abstract: In fishes, alterations to the natural flow regime are associated with divergence in body shape morphology compared with individuals from unaltered habitats. However, it is unclear whether this morphological divergence is attributable to evolutionary responses to modified flows, or is a result of phenotypic plasticity. Fishes inhabiting arid regions are ideal candidates for studying morphological plasticity as they are frequently exposed to extreme natural hydrological variability. We examined the effect of early exposure to flows on the development of body shape morphology in the western rainbowfish ( Melanotaenia australis ), a freshwater fish that is native to semiarid northwest Australia. Wild fish were collected from a region (the Hamersley Ranges) where fish in some habitats are subject to altered water flows due to mining activity. The offspring of wild‐caught fish were reared in replicated fast‐flow or slow‐flow channels, and geometric morphometric analyses were used to evaluate variation in fish body shape following 3, 6, 9, and 12 months of exposure. Water flows influenced fish morphology after 6 and 9 months of flow exposure, with fish in fast‐flow environments displaying a more robust body shape than those in slow‐flow habitats. No effect of flow exposure was observed at 3 and 12 months. Fishes also showed significant morphological variation within flow treatments, perhaps due to subtle differences in water flow among the replicate channels. Our findings suggest that early exposure to water flows can induce shifts in body shape morphology in arid zone freshwater fishes. Morphological plasticity may act to buffer arid zone populations from the impacts of anthropogenic activities, but further studies are required to link body shape plasticity with behavioral performance in habitats with modified flows. Abstract : Human impacts on natural habitats can result in artificially increased and sustained water flows. Using a freshwater fish from the arid zone, we show that fish can adjust their body shape in response to water flows experienced during development. This plasticity may act to buffer populations from human disturbances.